2020
DOI: 10.1080/13825585.2019.1708251
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cognitive training in older adults: be aware of CRUNCH

Abstract: Cognitive training research has revealed support for both the magnification and compensation accounts, respectively predicting larger or smaller training benefits for individuals already having strong cognitive abilities. A recent study in older adults (OAs) revealed evidence for the Compensation-Related Utilization of Neural Circuits Hypothesis, which best fits a magnification account. Only few studies examined working memory (WM) training gains in OAs as a function of initial executive functioning level. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 36 publications
2
6
0
Order By: Relevance
“…These results indicate that our intervention had a beneficial effect in maintaining attention abilities, providing support for its potential effectiveness in preventing cognitive decline in these domains. Our findings are consistent with gerontology studies, in which cognitive training and/or physical exercise training improved or preserved some, although not all, cognitive domains [ 29 31 ]. In a study with older adults, cognitive training showed a potential positive effect on executive function and other cognitive domains [ 30 ].…”
Section: Discussionsupporting
confidence: 92%
“…These results indicate that our intervention had a beneficial effect in maintaining attention abilities, providing support for its potential effectiveness in preventing cognitive decline in these domains. Our findings are consistent with gerontology studies, in which cognitive training and/or physical exercise training improved or preserved some, although not all, cognitive domains [ 29 31 ]. In a study with older adults, cognitive training showed a potential positive effect on executive function and other cognitive domains [ 30 ].…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, while it may be difficult to extrapolate the results from this small sample to the wider PD population, including those with more severe motor and CIs, this is also likely to represent the target demographic who may derive the most benefit from CT. In support of this, recent research supports that older adults with higher baseline cognitive function are more likely to benefit from CT than those who are already impaired (the so-called magnification effect) ( Mohlman et al, 2011 ; Fu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 88%
“…Evidence suggests that combined cognitive and motor training may lead to cognitive enhancement and improve the elderly’s independence. On the other hand, these exercises can lead to increased self-confidence, relaxation, and functional facilitation in the individual (Fu et al 2020 ; Joubert AND Chainay 2018 ). On the other hand, in quarantine conditions, it is recommended that sports activities be performed individually; this may prevent people from unnecessary gatherings (Qian and Jiang 2020 ).…”
Section: Introductionmentioning
confidence: 99%